Integration of film and game: multi-case study on narrative strategies in Hollywood movie gamification - Fang, Zhuxin (Frontiers in Sociology, 2025)
In order to explore the innovative approach to the integration of films and games, and to provide theoretical support and practical guidance for the development of gamified films, this essay uses the method of multi-case study to systematically sort out the unique gamified narrative strategies of three Hollywood films, Ready Player One, Free Guy, and Everything Everywhere All at Once, as well as the transmutations of aesthetics brought about by these narrative strategies, in terms of the dimensions of narrative approach, narrative mechanism, and immersive design, and so on. It is clear through the study that the narrative strategies of gamified films have had a profound impact on film creation and the film industry. It not only promotes the continuous innovation of film narrative structure and presentation methods, but also promotes the expansion and integration of the film and game industries.